TRIUMPH IN OVID: BETWEEN LITERARY TRADITION AND AUGUSTAN PROPAGANDA. (October 2022) - Gagliardi, Paola
Abstract : The Roman triumph is treated by the Augustan poets from a literary and political perspective. Ovid in particular gives it original and ambiguous features. The topic is often presented as the prediction of a triumph, a point of view perhaps inherited from Gallus. Propertius innovates from the Gallan original, and Ovid uses Propertius' treatment for further innovations. In his exile poetry, Ovid makes further substantial changes to the use of the triumph, which raises pointed questions as to the poet's sincerity in his apparent praise of Augustus and Tiberius.